Green Capabilities Mediate the Effect of Green Supply Chain Management Practices on Farmers Business Performance and Vegetable Non-Pesticide (Study on “Lestari” Women Farmer Group in Bantul Regency) - Indrianto, Anggraeni Pratama; Kusmantini, Titik; Sugandini, Dyah (Technium Social Sciences Journal, 2022)
The purpose of this research to find out and analyze the influence of Green Supply Chain Management consisting of Green Policy, Green Purchasing, and Green Packaging on Business Performance consisting of Environmental Performance and Economic Performance through Green Capabilities on non-pesticide fruit and vegetable farmers. The sampling technique used is the census method with a total of 60 respondents. Respondents in this study were all members of the KWT (Kelompok Wanita Tani/ Women Farmer Group) “Lestari” in Bantul Regency, Yogyakarta. The type of research conducted is survey research. The data analysis technique in this study was divided into descriptive analysis and quantitative analysis using Partial Least Square (PLS) analysis with the help of the SmartPLS 3.2.9 program. The results of this study indicate that Green Policy and Green Packaging have a significant positive effect on Business Performance; Green Purchasing has a significant negative effect on Business Performance; Green Policy and Green Purchasing have a significant positive effect on Green Capabilities; Green Packaging has a significant negative effect on Green Capabilities; and Green Policy and Green Purchasing have a significant positive effect on Business Performance through Green Capabilities.